Deformasi Koseismik dan Pascaseismik Gempa Yogyakarta 2006 dari Hasil Survei GPS - Abidin, Hasanuddin Z.; Andreas, H.; Meilano, I.; Gamal, M.; Gumilar, I.; Abdullah, C. I. (Geological Agency, 2009)
DOI:Â 10.17014/ijog.v4i4.87The Yogyakarta earthquake of 27 May 2006 occurred at 05:54 WIB with magnitude of 6.4 Mw. It shaked the region of Bantul, Yogyakarta, Sleman and Klaten for about 60 seconds. A week after the earthquake, i.e. 4-8 June 2006, a GPS survey was conducted on 48 GPS points belonging to the 2nd order national cadastral control network located in the earthquake affected region. The 2nd survey was conducted on 21-26 January 2008. The surveys were conducted using 14 dual-frequency geodetic type receivers and the Bernese 5.0 scientific software was used for data processing. The results of GPS surveys show that horizontal components of the co-seismic deformation of earthquake are generally about 10-15 cm or smaller. The GPS-derived displacement vectors and depths of aftershocks suggested the existence of left-lateral fault, with strike and dip angles of about 48o and 89o, located at about 5-10 km east of Opak Fault which is usually drawn along the Opak River. GPS surveys also estimate that horizontal components of the post-seismic deformation of Yogyakarta earthquake are about 0.3 to 9.1 cm between June 2006 and June 2008. While the co-seismic deformation shows the sinistral displacement, the post-seismic deformation indicates the dextral displacement of the eastern region of Opak Fault (Gunung Kidul area) which is relative to a more stable western region.